Noninvasive celiac plexus radiosurgery in palliative treatment for patients with symptomatic pancreatic cancer - Miszczyk, Marcin; Wydmański, Jerzy; Kocot-Kępska, Magdalena; Malec-Milewska, Małgorzata; Dolla, Łukasz; Miśta, Wioletta; Miszczyk, Leszek; Ben-Ailan, Maoz; Richard Lawrence, Yaacov (Contemporary Oncology/Współczesna Onkologia, 2021)
Advanced pancreatic cancer is commonly associated with significant visceral pain, radiating in a belt-like distribution to the upper abdomen, referring to the lower back, and significantly affecting patients’ quality of life (QoL). The pain is often poorly controlled by pharmacotherapy, or the doses necessary to control the pain produce substantial adverse effects. Other available pain management options include invasive celiac plexus block or neurolysis, palliative radiotherapy, and systemic chemotherapy, all with limited efficacy. In this case report, we present the first non-invasive celiac plexus radiosurgery performed in Europe in a patient with pancreatic cancer, demonstrating that significant pain relief can be achieved through a non-invasive procedure performed within 2 outpatient visits.